PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SMP PERTIWI 1 PADANG - abdulah abdulah (Jurnal Muara Pendidikan, 2018)
The problems that often arise in the learning process in class VII 1 SMP Pertiwi Padang showed low student participation. In working groups, many students who do not participate in the learning process, which the teacher. Cooperation between them, their peers in a group such as an opinion. So that the classroom atmosphere during the learning process becomes rigid, ineffective and boring for students. To overcome this teacher trying to implement an effective method of learning in the subjects of Citizenship Education. Such a way that can help students to participate during the learning process. Using a model of cooperative learning type games tournament teams. Formulation of the problem in this study were any obstacles faced by students in the application of cooperative learning model type games tournament teams on the subjects of citizenship education. The analysis showed that: 1) Cooperative learning model type teams tournament games can improve students' ability to think actively. 2) Model of cooperative learning type games tournament teams can stimulate children to think more actively. This type of study is a qualitative descriptive study, with the entire student population of Pertiwi 1 junior class VII Padang academic year 2011/2012 consisting of two classes. Sample of this study is the class VII.1 and VII.2 class. Based on the results of research and discussion of both classes, it can be concluded that the participation of students in the class of the group collaborated with the percentage of 71.83% VII.1 and VII.2 class with a percentage of 70.41% the result is quite good. His firm from research indicating that by applying a type of learning model kooperatip teams tournament games for Civic Education subjects, the study was conducted in class VII. Pertiwi 1 SMP Padang. So that students are capable of cooperating groups and students to think more actively in teaching and learning Citizenship Education that impact on learning outcomes for Civic Education.